3,4-Dichlorobenzoic acid biodegradation by the Edwardsiella tarda: Effect of Some Growth Conditions (Journal of Basic and Applied Research in Biomedicine, 2022)
The biodegradation of 3,4-DiChlorobenzoic acid was investigated by using Edwardsiella tarda and it used 3,4-DCBA as sole carbon and energy source. Several concentrations of 3,4-D CBAs (1mM, 2mM ,3mM ,4mM and 5mM) were used. The highest rate of degradation of 3,4-D CBAs was obtained at a concentration (2mM). The experiments were included substrate concentration, temperature, pH, starvation, adaptation, carbon and nitrogen sources. The degradation ability was monitored through the release of chloride disappearance of the substrate and finally the growth of bacterial cells on that substrate. The optimal temperature and pH for the bacteria were 42ºC and 7.5, respectively. Adaptation of the cells on 3,4-DCBA for 48 hours and cells starvation for 24 hours and 48 hours increasing the initial degradation rate. The carbon sources affected the 3,4 –DCBA degradation differently from that on chloride and cell mass production. Nitrogen sources supplied (yeast extract, L-proline, casein, NH4, K-Nitrate, arginine, urea and glycine). Urea and casine caused a repression in 3,4-DCBA degradation. Catechol 1,2 dioxygenase activity was found to be present in cell free extracts suggesting that 3,4-DCBA is catabolized by ortho-ring cleavage pathway.